Real‐world effectiveness and safety of tildrakizumab in long‐term treatment of plaque psoriasis: Results from the non‐interventional, prospective, multicentre study TILOT. (23rd September 2022) - Tsianakas, Athanasios; Schwichtenberg, Uwe; Pierchalla, Peter; Hinz, Torsten; Diemert, Sebastian; Korge, Bernhard
Abstract: Background: Plaque psoriasis is a chronic inflammatory disorder affecting the skin and impacting quality of life. Tildrakizumab (TIL) is an IL‐23 inhibitor licensed for moderate‐to‐severe plaque psoriasis. Regulatory approval of medicinal products is based on safety and efficacy data from randomized controlled trials (RCTs) which impose stringent selection criteria. Long‐term non‐interventional studies (NIS) are needed to establish effectiveness and safety in daily practice bridging the gap between RCTs and the real‐world setting. Objectives: This analysis of the NIS TILOT seeks to evaluate effectiveness and safety of TIL in patients with moderate‐to‐severe plaque psoriasis in a real‐world setting. Secondary objectives include the assessment of the Dermatology Life Quality Index (DLQI), treatment satisfaction and course of scalp and nail disease using Physician Global Assessment (PGA). Methods: Interim analysis at 52 weeks (W) of the ongoing non‐interventional, prospective, long‐term multicentre study TILOT. Results: The effectiveness analysis included 412 patients. The mean [standard deviation, SD] Psoriasis Area and Severity Index (PASI) score was 16.0 [9.1] at baseline improving by 82.4% (95% confidence interval [CI], 78.9–86.0) to 2.1 [2.9] at W52. The proportion of patients achieving PASI scores of <3 and <5 increased over time peaking at 74.6% (95% CI, 69.3–79.4) and 88.4% (95% CI, 84.3–91.8) at W52. Scalp‐PGA and nail‐PGA improved by 79.8% (95% CI, 75.6–84.0) and 72.7% (95% CI, 63.9–81.6), respectively. DLQI of 0/1 was achieved by 48.2% (95% CI, 42.3–54.2). Nine out of 10 physicians and patients expressed a high level of treatment satisfaction. No new safety signals were observed. Conclusions: This prospective cohort study demonstrates a high degree of effectiveness and a reassuring safety profile of TIL in a real‐world setting over 52 weeks. Patients with scalp and nail involvement or pruritus showed marked improvements.